Analisis Pemilihan Supplier Bibit Ayam dengan Metode AHP dan (TOPSIS) (Studi Kasus: Peternakan Ayam X) - Arini, Candra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This study was conducted at X poultry farm in Bontang, East Kalimantan, which faces recurring problems such as high mortality of broiler chicks, mismatched order quantities, and chicks that are deformed or vulnerable to disease. The objective of this research is to identify the criteria for selecting chick suppliers and to determine the best supplier based on these criteria. Data were collected through interviews with the farm owner and questionnaires, and were analyzed using the Analytical Hierarchy Process (AHP) to calculate the weights of criteria and sub-criteria, as well as the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) to rank the suppliers. The AHP results showed that quality (0.572) was the most important criterion, followed by delivery (0.257), price (0.115), and service (0.056). The key sub-criterion was disease resistance (0.833). Based on TOPSIS, the best supplier was supplier D, followed by supplier O and supplier K.